Answer:
y2-y1/x2-x1
Step-by-step explanation:
x1= -4 x2= -5
y1= 8 y2= -6
-6-8/-5+4=14
so M = 14
y-y1=m(x-x1)
y-8=14(x+4)
8y=14x+56
rearrange
-14x+8y=56
but you need it in the form of AX+BX=C (THE X SHOULD BE POSITIVE SO CHNAGE ALL THE SIGNS )
14X-8Y=-56
Answer:2/3
Step-by-step explanation:
Simplifying
(9m + -6) * 7 = 0
Reorder the terms:
(-6 + 9m) * 7 = 0
Reorder the terms for easier multiplication:
7(-6 + 9m) = 0
(-6 * 7 + 9m * 7) = 0
(-42 + 63m) = 0
Solving
-42 + 63m = 0
Solving for variable 'm'.
Move all terms containing m to the left, all other terms to the right.
Add '42' to each side of the equation.
-42 + 42 + 63m = 0 + 42
Combine like terms: -42 + 42 = 0
0 + 63m = 0 + 42
63m = 0 + 42
Combine like terms: 0 + 42 = 42
63m = 42
Divide each side by '63'.
m = 0.6666666667
Simplifying
m = 0.6666666667=2/3 when simplified
Answer:
324352
Step-by-step explanation: